2023
DOI: 10.1192/bjo.2023.567
|View full text |Cite
|
Sign up to set email alerts
|

Homicide in the context of psychosis: analysis of prior service utilisation and age at onset of illness and violence

Stephanie R. Penney,
Austin A. Lam,
Nathan Kolla
et al.

Abstract: Background Public stigma and fear are heightened in cases of extreme violence perpetrated by persons with serious mental illness (SMI). Prevention efforts require understanding of illness patterns and treatment needs prior to these events unfolding. Aims To examine mental health service utilisation by persons who committed homicide and entered into forensic care, to investigate the adequacy of mental healthcare preceding these offences. Method Forensic patients across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In contrast, in the United Kingdom, a person can be diverted from a custodial sentence to hospital for treatment by a court under the Mental Health Act 1983 , and this can occur at both the pre- and postsentencing stages of the criminal justice process (Ministry of Justice UK, 2021). In addition to limited criminal justice diversion opportunities, community mental health services often fail to meet the needs of people with mental illness before they become involved in crime in Canada (Penney et al, 2023). A study of all people found NCR in three Canadian provinces over 5 years found that most people who were found NCR had been under the purview of the civil psychiatric system with a median of two prior civil psychiatric hospitalizations (Crocker et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the United Kingdom, a person can be diverted from a custodial sentence to hospital for treatment by a court under the Mental Health Act 1983 , and this can occur at both the pre- and postsentencing stages of the criminal justice process (Ministry of Justice UK, 2021). In addition to limited criminal justice diversion opportunities, community mental health services often fail to meet the needs of people with mental illness before they become involved in crime in Canada (Penney et al, 2023). A study of all people found NCR in three Canadian provinces over 5 years found that most people who were found NCR had been under the purview of the civil psychiatric system with a median of two prior civil psychiatric hospitalizations (Crocker et al, 2015).…”
Section: Discussionmentioning
confidence: 99%